The Expression Profile of MicroRNAs in Small and Large Abdominal Aortic Aneurysms - Václava Černá; Pavel Ostašov; Pavel Pitule; Jiří Moláček; Vladislav Třeška; Martin Pešta (Cardiology Research and Practice)
Background. Abdominal aortic aneurysms (AAA) are relatively frequent in elderly population, and their ruptures are related with high mortality rate. There are no actually used laboratory markers predicting the AAA development, course, and rupture. MicroRNAs are small noncoding molecules involved in posttranscriptional gene expression regulation, influencing processes on cell and tissue levels, and are actually in focus due to their potential to become diagnostic or prognostic markers in various diseases. Methods. Tissue samples of AAA patients and healthy controls were collected, from which miRNA was isolated. Microarray including the complete panel of 2549 miRNAs was used to find expression miRNA profiles that were analysed in three subgroups: small (N = 10) and large (N = 6) aneurysms and healthy controls (N = 5). Fold changes between expression in aneurysms and normal tissue were calculated including corresponding p values, adjusted to multiple comparisons. Results. Six miRNAs were found to be significantly dysregulated in small aneurysms (miR-7158-5p, miR-658, miR-517-5p, miR-122-5p, miR-326, and miR-3180) and 162 in large aneurysms, in comparison with the healthy control. Ten miRNAs in large aneurysms with more than two-fold significant change in expression were identified: miR-23a-3p, miR-24-3p, miR-27a-3p, miR-27b-3p, miR-30d-5p, miR-193a-3p, miR-203a-3p, miR-365a-3p, miR-4291, and miR-3663-3p and all, but the last one was downregulated in aneurysmal walls. Conclusion. We confirmed some previously identified miRNAs (miR-23/27/24 family, miR-193a, and miR-30) as associated with AAA pathogenesis. We have found other, yet in AAA unidentified miRNAs (miR-203a, miR-3663, miR-365a, and miR-4291) for further analyses, to investigate more closely their possible role in pathogenesis of aneurysms. If their role in AAA development is proved significant in future, they can become potential markers or treatment targets.